P139 Impact of nebulised hypertonic saline using positive expiratory pressure on exacerbations in adults with large airway collapse with symptoms (LACS). (December 2018) - Sheehan, RL; Abu-El-Hawa, NS; Tavernier, G; Fowler, SJ; Niven, R
Abstract : Introduction: Large Airway Collapse with Symptoms (LACS), characterised by collapse of large airways during expiration, may cause dyspnoea, intractable cough and mucous trapping, resulting in recurrent infective exacerbations and protracted hospital stays. Nebulised hypertonic saline (HTS) has been shown to reduce infective exacerbations in other patient groups. We hypothesised that supporting the airways using positive expiratory pressure (PEP) during inhalation of HTS would improve drug deposition and sputum clearance and be associated with a reduction in the number of exacerbations in patients with LACS. Methods: We collected data on infective exacerbations in patients with LACS (confirmed by bronchoscopy) for the twelve months pre and post commencing treatment with HTS via the Pari PEP nebuliser device, and analysed the mean reduction in year-normalised exacerbation frequency using a non-parametric Wilcoxon test. Results: Data on sixty-nine patients commencing treatment with HTS between January 2017 and May 2018 were available. Mean (SD) age 58.4 (14.6) yrs, BMI 34.8 (5.3) kg/m 2, 83% female, 91% with comorbid and asthma and 47% bronchiectasis. Long term treatment included CPAP in 46% and antibiotics in 39%. Mean (min-max) annualised exacerbation rate in the 12 months prior to commencement of HTS was 4 (0–28) compared to 2.8 (0–7) in the patients after starting treatment, amounting to a 30% fall in annualised exacerbation rate (p=0.039, see figure 1). Conclusion: Use of HTS delivered by PEP nebuliser device significantly reduced rate of exacerbations in patients with LACS in our study. Further research following-up these patients will determine long-term results with a larger sample size as more patients are commenced on treatment.